The role and clinical significance of programmed cell death- ligand 1 expressed on CD19+B-cells and subsets in systemic lupus erythematosus - Jia, Xiao-Yun (Clinical immunology (Orlando, Fla.), 2019)
Copyright © 2018 Elsevier Inc. All rights reserved.